Pengembangan Media Pembelajaran E-Book Biologi pada Materi Sistem Reproduksi Manusia di Kelas XI - Husnul Khatimah Hadir (UNM Journal of Biological Education, 2023)
This study is a development research that aims to produce a product in the form of a Biology e-book learning media on human reproductive system material. This development research refers to the development model of Alessi & Trollip’s model which consists of three stages, namely planning, design, and development. The research instruments used were instrument validation sheets, teacher’s response questionnaire, students’ questionnaires, and learning outcomes test. The samples in this study were students of grade XI at SMK Kesehatan Yapika Makassar (Vocational High School of Health at Yapika Makassar). Based on the results of data analysis, it shows that: 1) the Biological e-book learning media on human reproductive system material meets the valid criteria with a mean score of 4.8 (valid), 2) the Biology e-book learning media on human reproductive system material meets the practical criteria based on the results of the teacher's response by 80.71% (very positive) and the result of the students’ responsesby 78.70% (positive), and 3) the Biology e-book learning media on human reproductive system material meets the effective criteria with the percentage of completeness of learning outcomes by 75% (good). Based on the results of the study, it can be concluded that the Biological e-book learning media on human reproductive system material has met valid, practical, and effective criteria.